Socio-economic correlates of childhood obesity in urban and rural England - Titis, Elzbieta; Di Salvatore, Jessica; Procter, Rob (Public health nutrition, 2023)
Physical access to food may affect diet and thus obesity rates. We build upon existing work to better understand how socio-economic characteristics of locations are associated with childhood overweight. Using cross-sectional design and publicly available data, the study specifically compares rural and urban areas, including interactions of distance from supermarkets with income and population density. We examine cross-sectional associations with obesity prevalence both in the national scale and across urban and rural areas differing in household wealth. Children in reception class (aged 4-5) from all state-maintained schools in England taking part in the National Child Measurement Programme ( 6772). Income was the main predictor of childhood obesity (adj. R-sq=.316, p<.001), whereas distance played only a marginal role (adj. R-sq=.01, p<.001). In urban areas, distance and density correlate with obesity directly and conditionally. Urban children were slightly more obese, but the opposite was true for children in affluent areas. Association between income poverty and obesity rates was stronger in urban areas (7·59 %) than rural areas (4·95 %), the former which also showed stronger association between distance and obesity. Obesogenic environments present heightened risks in deprived urban and affluent rural areas. The results have potential value for policy making as for planning and targeting of services for vulnerable groups.